The Constitution and the Right to Education: An Analysis of Constitutional Law Perspectives - Yulfa Mulyeni (Universitas Muhammadiyah Palu, 2024)
This study aims to analyze the regulation and implementation of the right to education in the constitution with a focus on the perspective of constitutional law. This study uses a qualitative method with a case study approach, examining the Indonesian constitution as well as international comparisons with countries that have advanced education systems such as Finland and Japan. The results show that although the right to education is recognized in the constitution, its implementation in Indonesia still faces various challenges, including unequal access to and quality of education. The Constitutional Court has an important role in upholding this right through significant decisions. International case studies provide insights into best practices that can be adopted to strengthen the national education system. The proposed policy recommendations include increased budget allocations, continuous training for teachers, equitable development of education infrastructure, enforcement of anti-discrimination policies and increased collaboration between the government, communities and the private sector. This research makes an important contribution in understanding the dynamics of constitutional law related to the right to education and offers solutions to improve its implementation in Indonesia.